1993
DOI: 10.1111/j.1751-1097.1993.tb02338.x
|View full text |Cite
|
Sign up to set email alerts
|

ACTION SPECTRA FOR THE trans TO cis PHOTOISOMERISATION OF UROCANIC ACID in vitro and IN MOUSE SKIN

Abstract: Urocanic acid (UCA) is a major UV chromophore in the upper layers of the skin where it is found predominantly as the trans isomer. UV irradiation induces photoisomerisation of trans-UCA to cis-UCA which has been shown to mimic some of the immunosuppressive properties of UV exposure. We examined the wavelength dependence for trans-UCA to cis-UCA photoisomerisation in vitro and in mouse skin in vivo over the spectral range 270-340 nm. The resulting action spectra were very similar with maximal effectiveness at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 13 publications
5
62
1
Order By: Relevance
“…Indeed, when weighted for the solar spectral output, the most effective photoisomerization wavelength in human skin is 326 nm (3). In addition the action spectrum for the isomerization of UCA in mouse skin in vivo has been constructed and has a peak of 300-310 nm (4). Therefore the relationship between the formation of cis-UCA and effects on the immune system is likely to be complex and may involve, for example, a cascade of responses initiated by the isomerization or cis-UCA acting at a site other than the site of isomerization.…”
Section: Chromophore For Uv-induced Immunosuppression: Urocanic Acid mentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, when weighted for the solar spectral output, the most effective photoisomerization wavelength in human skin is 326 nm (3). In addition the action spectrum for the isomerization of UCA in mouse skin in vivo has been constructed and has a peak of 300-310 nm (4). Therefore the relationship between the formation of cis-UCA and effects on the immune system is likely to be complex and may involve, for example, a cascade of responses initiated by the isomerization or cis-UCA acting at a site other than the site of isomerization.…”
Section: Chromophore For Uv-induced Immunosuppression: Urocanic Acid mentioning
confidence: 99%
“…The development of these tumors presumably results from transforming events induced in keratinocyte targets as a consequence of exposure to UVR. However, work over the past two decades has demonstrated that, at least in mice, most UVR-induced skin tumors are highly immunogenic and regress upon transfer to syngeneic recipients (3,4). This, of course, raises the question as to why these tumors develop and grow in the primary host.…”
Section: Is There a Role For Cis-uca In Cutaneous Carcinogenesis?mentioning
confidence: 99%
See 2 more Smart Citations
“…Of these compounds, UCA has attracted an attention in dermatology and cosmetics fields as a natural sunscreen since it was identified as the major acid-soluble, UVabsorbing compound in the stratum corneum [19,20]. The photon energy absorbed by UCA is effectively dissipated through the reversible isomerization to cis-urocanic acid [21,22]. However, UCA's reputation as an ideal natural sunscreen was shattered by the observations that cis-urocanic acid mediated the immunosuppressive effect of UV [23], and UCA increased the photocarcinogenic risk in hairless mice [24].…”
Section: Introductionmentioning
confidence: 99%